Altered Effective Connectivity of Children and Young Adults With Unilateral Amblyopia: A Resting-State Functional Magnetic Resonance Imaging Study - Dai, Peishan; Zhou, Xiaoyan; Ou, Yilin; Xiong, Tong; Zhang, Jinlong; Chen, Zailiang; Zou, Beiji; Wei, Xin; Wu, Ying; Xiao, Manyi (Frontiers in Neuroscience, 2021)
The altered functional connectivity in amblyopia has been investigated by many studies, but the specific causality of brain connectivity needs to be explored further to understand the brain activity of amblyopia. We investigated whether the effective connectivity of children and young adults with amblyopia was altered. The subjects included 16 children and young adults with left eye amblyopia and 17 healthy controls. The abnormalities between the left/right primary visual cortex and the other brain regions were investigated in a voxel-wise manner using the Granger causality analysis. According to the effective connectivity results in the healthy controls and the distribution of visual pathways, 12 regions of interest were selected to construct an effective connectivity network. The alteration of the effective connectivity network of the children and young adults with amblyopia was analyzed. In the voxel-wise manner analysis, amblyopia showed significantly decreased effective connectivity between the left/right of the primary visual cortex and the left middle frontal gyrus/ left inferior frontal gyrus compared with the healthy controls. In the effective connectivity network analysis, compared with the healthy controls, amblyopia showed significantly decreased effective connectivity from the left calcarine fissure, posterior cingulate gyrus, left lingual gyrus, right lingual gyrus, and right fusiform gyrus to the right calcarine fissure. Amblyopia also showed significantly decreased effective connectivity from the right inferior frontal gyrus and right lingual gyrus to the left superior temporal gyrus compared with the healthy controls in the effective connectivity network analysis. The results may indicate amblyopia altered the visual feedforward and feedback pathway, and amblyopia may have a greater relevance with the feedback pathway than the feedforward pathway. Amblyopia may also correlate with the feedforward of the third visual pathway.